2018
DOI: 10.1111/jnc.14608
|View full text |Cite
|
Sign up to set email alerts
|

Wnt‐induced activation of glucose metabolism mediates the in vivo neuroprotective roles of Wnt signaling in Alzheimer disease

Abstract: Dysregulated Wnt signaling is linked to major neurodegenerative diseases, including Alzheimer disease (AD). In mouse models of AD, activation of the canonical Wnt signaling pathway improves learning/memory, but the mechanism for this remains unclear. The decline in brain function in AD patients correlates with reduced glucose utilization by neurons. Here, we test whether improvements in glucose metabolism mediate the neuroprotective effects of Wnt in AD mouse model. APPswe/PS1dE9 transgenic mice were used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 95 publications
(167 reference statements)
1
61
0
Order By: Relevance
“…Considerable research has examined the associations between AD and the enzymes intimately linked to glycolysis (i.e., hexokinase, glyceraldehyde 3-phosphate dehydrogenase [GAPDH], and pyruvate kinase [PK]) (Vallee et al, 2018b;Wu et al, 2018;Butterfield and Halliwell, 2019). Cisternas et al (2019) reported that Wnt signaling promotes glucose metabolism by increasing the expression of hexokinase and PFK, which causes neuroprotective effects. However, decreased hexokinase and PFK expression and dysregulated Wnt signaling are observed in AD.…”
Section: Altered Glycolysis In Aging and Admentioning
confidence: 99%
“…Considerable research has examined the associations between AD and the enzymes intimately linked to glycolysis (i.e., hexokinase, glyceraldehyde 3-phosphate dehydrogenase [GAPDH], and pyruvate kinase [PK]) (Vallee et al, 2018b;Wu et al, 2018;Butterfield and Halliwell, 2019). Cisternas et al (2019) reported that Wnt signaling promotes glucose metabolism by increasing the expression of hexokinase and PFK, which causes neuroprotective effects. However, decreased hexokinase and PFK expression and dysregulated Wnt signaling are observed in AD.…”
Section: Altered Glycolysis In Aging and Admentioning
confidence: 99%
“…Wnt signaling is known to be impaired in AD [109][110][111], and activation of the Wnt/β-catenin signaling pathway represses BACE-1 expression [112]. Activation of Wnt signaling has been shown to rescue memory loss and improves synaptic dysfunction in APP/PS1 AD transgenic mice [113,114]. In the well-known canonical Wnt signaling pathway, Wnt's binding to its receptor Frizzled and the downstream processes leading to the stabilization of β-catenin involves the inhibition of GSK-3β [115].…”
Section: Enhancement Of Aβ and Tau Expression Modification And Clearmentioning
confidence: 99%
“…Hyperphosphorylated Tau accumulates in paired helical filaments (PHF) and leads to the formation of neurofibrillary tangles as well as neuronal degeneration in AD (Alonso et al, 1996). Several studies point to a possible role for Wnt in AD (Cisternas et al, 2019;Hu et al, 2019;Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%